Incidence of guava (Psidium guajava L.) wilt caused by Fusarium oxysporum sch. f. sp. psidii in Bangladesh - Hussain, M Zakir; Rahman, MA; Bashar, MA (Journal of the Asiatic Society of Bangladesh, Science, 2014)
A survey was conducted in eighteen orchards in respect of incidence of guava wilt caused by Fusarium oxysporum f. sp. psidii located in eight districts of Bangladesh. Observation of 2907 plants yielded 22.94% wilt in an average irrespective of varieties. The highest wilting (50%) was found in the Agricultural Research Station, Thakurgaon on cv. Kazi peyara followed by 34.78% on cv. BARI peyara-2 at Gazipur; 32.39% on cv. Mukundapuri in Brahmanbaria, 22.58% on cv. Kazi peyara in Faridpur, and 17.24% on cv. Kanchannagar in Chittagong and 12.50% on cv. Swarupkathi in the Pirojpur district, whereas the lowest percentage (8%) of wilted plants were observed on cv. BARI peyara- 2 and cv. Kazi peyara at the RARS, Rahmatpur, Barisal, and at Pahartali, Chittagong. After initiation of wilt symptom, it took 15 to 170 days for completion of wilt in 2006. Wilting was recorded 25.51% within the first 30 days and 78.57% cumulative wilting was recorded after 60 days in 2006. Higher wilt incidence was recorded in August, September and October, whereas remarkable decrease of the disease was recorded during winter i.e. November and December in both the years. J. Asiat. Soc. Bangladesh, Sci. 40(1): 97-105, June 2014